Marine Mammal Acoustics in a Noisy Ocean - Erbe, Christine; Houser, Dorian; Bowles, Ann.; Porter, Michael B.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open-access book invites its readers to dive into the depths of marine mammal bioacoustics. The ocean is a noisy place$1 (Bnaturally as well as anthropogenically. Our book explores the fundamentals of ocean acoustics, revealing the intricate sources of underwater noise that challenge marine life. Readers delve into the unique vocalizations of mysticetes, odontocetes, pinnipeds, otters, and sirenians, uncovering their diverse communication in stormy waters. The book presents research on marine mammal hearing and the impact of noise on their physiology and behavior, from the subtle behavioral responses to the broader biological significance of these effects. With insights into the management of anthropogenic noise, this book equips students, researchers, environmental managers, policy makers, conservationists, and enthusiasts alike with vital knowledge for protecting our ocean$1 (Bs acoustic environments.s
Chapter 1. Fundamentals of Ocean Acoustics -- Chapter 2. Sources of Underwater Noise -- Chapter 3. Mysticete Sounds -- Chapter 4. Odontocete Sounds -- Chapter 5. Pinniped Sounds -- Chapter 6. Otter Sounds -- Chapter 7. Sirenian Sounds -- Chapter 8. Marine Mammal Hearing -- Chapter 9. Physiological Effects of Sound on Marine Mammals -- Chapter 10. Behavioral Responses to Underwater Noise -- Chapter 11. Biological Significance of Responses to Noise -- Chapter 12. Management of Noise.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Freshwater ecology; Marine ecology; Zoology; Physiology; Neurophysiology; Animal migration; Anatomy, Comparative; Freshwater and Marine Ecology; Zoology; Animal Physiology; Neurophysiology; Animal Migration; Animal Anatomy